2021
DOI: 10.1016/j.actamat.2021.117222
|View full text |Cite
|
Sign up to set email alerts
|

Multiple coupling modes to relax shear strain during grain boundary migration

Abstract: Shear-coupled grain boundary (GB) migration is an effective plastic mechanism in absence of dislocation activity, ie. more favorably in nanocrystalline metals. For a given GB, several stress induced migration mechanisms, referred as coupling modes participate to the decrease of the elastic energy produced by the shear. They operate through the nucleation and motion of interfacial defects known as disconnections, carrying elementary shear strain characterized by their Burgers vector. However, so far, the coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
(86 reference statements)
1
1
0
Order By: Relevance
“…between the Burgers vector direction of Shockley disconnections, the coupling factor could be either reduced to 0 or inverted. In a past article, we indeed have shown that alternative coupling modes could be activated when the shear stress is properly chosen [5,7]. The present observation tends to indicate that in addition, modes carrying the same shear but with opposite migration directions can coexist, presumably because the probability rate to nucleate simple or double steps is similar at least at high temperature.…”
Section: σ3 Gb Migrationsupporting
confidence: 69%
See 1 more Smart Citation
“…between the Burgers vector direction of Shockley disconnections, the coupling factor could be either reduced to 0 or inverted. In a past article, we indeed have shown that alternative coupling modes could be activated when the shear stress is properly chosen [5,7]. The present observation tends to indicate that in addition, modes carrying the same shear but with opposite migration directions can coexist, presumably because the probability rate to nucleate simple or double steps is similar at least at high temperature.…”
Section: σ3 Gb Migrationsupporting
confidence: 69%
“…Second, observed interactions between dislocations and GB plane (Figs. 5,7,9) have shown that most probable slip systems, i.e. with a high Schmid factor, lead to M = 0.41 largely smaller than 1.…”
Section: Interactions Reactions and Transmissionmentioning
confidence: 99%